2009
DOI: 10.1016/j.biortech.2009.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of influent nutrient ratios and hydraulic retention time (HRT) on simultaneous phosphorus and nitrogen removal in a two-sludge sequencing batch reactor process

Abstract: A laboratory-scale anaerobic-anoxic/nitrification sequencing batch reactor (A(2)N-SBR) fed with domestic wastewater was operated to examine the effect of varying ratios of influent COD/P, COD/TN and TN/P on the nutrient removal. With the increased COD/P, the phosphorus removals exhibited an upward trend. The influent TN/P ratios had a positive linear correlation with the phosphorus removal efficiencies, mainly because nitrates act as electron acceptors for the phosphorus uptake in the A(2)N-SBR. Moreover, it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(46 citation statements)
references
References 29 publications
7
37
0
2
Order By: Relevance
“…Similar results are also reported by Wang et al [25] concerning the operation of an A 2 N-SBR treating municipal wastewater, where P removal percentage increased form 62% to 97% by increasing the influent COD/P ratio between 9.5 and 30.8. In the same study, it was also suggested that increase of the COD/P ratio to values greater than 20 g/g resulted in no further improvement of the system phosphorus removal efficiency, mainly because PAOs have reached their maximum capacity of storing PHAs.…”
Section: Effect Of Cod/p Ratiosupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results are also reported by Wang et al [25] concerning the operation of an A 2 N-SBR treating municipal wastewater, where P removal percentage increased form 62% to 97% by increasing the influent COD/P ratio between 9.5 and 30.8. In the same study, it was also suggested that increase of the COD/P ratio to values greater than 20 g/g resulted in no further improvement of the system phosphorus removal efficiency, mainly because PAOs have reached their maximum capacity of storing PHAs.…”
Section: Effect Of Cod/p Ratiosupporting
confidence: 90%
“…However, respective studies concerning the phosphorus removal under anoxic conditions are limited [24,25]. Furthermore, even these investigations were conducted in SBRs, the flow characteristics of which are substantially different when compared to continuous-flow systems, usually incorporated in practical implementations.…”
Section: Introductionmentioning
confidence: 97%
“…The operating parameters of SND processes, such as oxygen concentration (Hocaoglu et al 2011), temperature (Zhang et al 2009), and C/N ratio (Chiu et al 2007), were found to significantly affect microbial metabolisms, and consequently nutrient removal performance. C/P ratio is reported to significantly influence the nutrients removal and is an essential factor for the optimization of wastewater treatment process, such as anaerobic-anoxic/nitrification sequencing batch reactor (A 2 N-SBR) (Wang et al 2009), UniFed SBR process (Zhao et al 2008), and SND process (Ge et al 2010, Jia et al 2013a. However, to date, special attempts have not yet been devoted to investigating the impact of chemical oxygen demand (COD)/ total phosphorus (TP) ratio on the performance of SND processes in terms of microbial community characteristics.…”
Section: Responsible Editor: Robert Duranmentioning
confidence: 99%
“…The performance and microbial community of bioreactor can be affected by many influencing factors, such as nutrient content (Rene et al 2008), anoxic/aerobic phase fraction (Hu et al 2011), salinity , solid retention time (Moussa et al 2005), and hydraulic retention time (HRT) (Kargi and Uygur 2003). Among the above-mentioned influencing factors, HRT is regarded as one of important operating parameters affecting the performance and microbial community of bioreactor (Wang et al 2009). Li et al (2013) investigated the effects of HRT on the nitrification activities and population dynamics of a conventional activated sludge system fed with synthetic inorganic wastewater, and they found that a short HRT strengthened the dominant position of the fastgrowing Nitrosomonas sp., which was responsible for the increase in the specific ammonium oxidation rate with the decrease in HRT.…”
Section: Introductionmentioning
confidence: 99%